2011
DOI: 10.1016/j.ccr.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

An Fcγ Receptor-Dependent Mechanism Drives Antibody-Mediated Target-Receptor Signaling in Cancer Cells

Abstract: Antibodies to cell-surface antigens trigger activatory Fcγ receptor (FcγR)-mediated retrograde signals in leukocytes to control immune effector functions. Here, we uncover an FcγR mechanism that drives antibody-dependent forward signaling in target cells. Agonistic antibodies to death receptor 5 (DR5) induce cancer-cell apoptosis and are in clinical trials; however, their mechanism of action in vivo is not fully defined. Interaction of the DR5-agonistic antibody drozitumab with leukocyte FcγRs promoted DR5-med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
231
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(245 citation statements)
references
References 81 publications
(116 reference statements)
9
231
2
Order By: Relevance
“…We and others have recently found that both agonistic αCD40 and αDR5 antibodies require Fc-FcγR interactions for their in vivo activities and, in contrast to cytotoxic effector antitumor antibodies, these agonistic antibodies require no activating FcγRs, but inhibitory FcγRIIB (14)(15)(16). These studies, together with previous and other recent studies (17,18), have established a general requirement of FcγRIIB for the in vivo activities of agonistic anti-TNFR antibodies (19). In addition, we have also demonstrated that Fcs that preferentially bind to inhibitory FcγRIIB are more potent for agonistic anti-TNFR antibodies, and that the potency of agonistic anti-TNFR antibodies can be enhanced through FcγRIIB-targeted Fc engineering (14,15).…”
mentioning
confidence: 71%
“…We and others have recently found that both agonistic αCD40 and αDR5 antibodies require Fc-FcγR interactions for their in vivo activities and, in contrast to cytotoxic effector antitumor antibodies, these agonistic antibodies require no activating FcγRs, but inhibitory FcγRIIB (14)(15)(16). These studies, together with previous and other recent studies (17,18), have established a general requirement of FcγRIIB for the in vivo activities of agonistic anti-TNFR antibodies (19). In addition, we have also demonstrated that Fcs that preferentially bind to inhibitory FcγRIIB are more potent for agonistic anti-TNFR antibodies, and that the potency of agonistic anti-TNFR antibodies can be enhanced through FcγRIIB-targeted Fc engineering (14,15).…”
mentioning
confidence: 71%
“…Furthermore, TRAIL-induced apoptosis can proceed independent of protein neosynthesis, explaining why a systems analysis of baseline protein expression is sufficient to predict TRAIL responsiveness. As TRAIL ligands are currently investigated in clinical trials and as improved second generation ligands are currently in preclinical development, 30,31 our systems approach may provide possibilities to identify TRAIL-responsive melanoma by molecular profiling, and by extension may assist in patient stratification as part of future clinical trial designs. We also predicted DTIC-induced cell death, albeit with slightly lower accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…22 Antibody crosslinking by immune cells expressing Fcg-receptors such as leukocytes can be therapeutically beneficial by triggering pro-apoptotic stimuli in cancer cells. 21 This effect can be mimicked in vitro by using an anti-Fc antibody, such as a polyclonal goat anti-human IgG, AbXL.…”
Section: Ign523 Elicits Caspase-dependent Apoptosis Increases Lysosomentioning
confidence: 99%